2007
DOI: 10.1093/humrep/dem339
|View full text |Cite
|
Sign up to set email alerts
|

Live birth rates after transfer of equal number of blastocysts or cleavage-stage embryos in IVF. A systematic review and meta-analysis

Abstract: The best available evidence suggests that the probability of live birth after fresh IVF is significantly higher after blastocyst-stage embryo transfer as compared to cleavage-stage embryo transfer when equal number of embryos are transferred in the two groups compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
127
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(138 citation statements)
references
References 32 publications
4
127
0
7
Order By: Relevance
“…In addition, oocyte donors are typically young women with good ovarian reserve, thus embryos should characteristically be healthy with good implantation potential. Recent studies have shown that blastocyst stage embryo transfer is associated with higher implantation and pregnancy rates [27]. The explanation for this finding is twofold.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, oocyte donors are typically young women with good ovarian reserve, thus embryos should characteristically be healthy with good implantation potential. Recent studies have shown that blastocyst stage embryo transfer is associated with higher implantation and pregnancy rates [27]. The explanation for this finding is twofold.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta analysis demonstrated that the probability of live birth following fresh IVF is higher after blastocyst-stage embryo transfer compared to cleavage-stage transfer (Evidence 1a) (Papanikolaou et al, 2008). In the USA, for the year 2005 in women over 40, success rates for day 5 embryo transfers were higher than for day 3 in women over 40.…”
Section: Blastocyst Tranfermentioning
confidence: 99%
“…In addition, data analysis also supporting the implementation of day 5 embryo transfer as it has better success rates in all age groups including women over 40. But these results do not include the cycles that a day 5 blastocyst failed to develop (CDC 2005;Papanikolaou et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Data analysis shows that the implementation of day 5 embryo transfer improves the IVF success rates in all age groups, including women over 40. However, the included studies did not consider the cycles that a blastocyst failed to develop (Papanikolaou et al 2008). Merely reaching the blastocyst stage of embryo development is a good prognostic factor.…”
mentioning
confidence: 99%